Obstacles and challenges to the national narcotics agency (BNN) of papua province in managing drugs trafficing and illicity goods (case study in Jayapura city) - Melyana Ratana Pugu; Made Selly Dwi Suryanti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to analyze the obstacles and challenges faced by the Papua Province National Narcotics Agency (BNN) in dealing with the trafficking of drugs and illegal goods in Jayapura City, Papua Province. The phenomenon of transnational crime is increasingly strengthened by the development of globalization, which has resulted in the blurring of national boundaries. One form of this crime is drug smuggling. This research was conducted using qualitative methods because the data presented is based on interviews and observations, so the results obtained are objective and actual. The results of this study show that eradicating the abuse and illicit trafficking of drugs cannot be done by just one person and requires cooperation from various elements of society and other parties such as the police and customs. BNN Papua has made various efforts to ensure that drug abuse and illicit trafficking disappear from Indonesia. Some of the activities carried out include educating the public, rehabilitating former users, and eradicating narcotics smuggling.